Built Environment Professionals' Perceptions Of The Effectiveness Of Building Control Measures In Lagos State - Ojelabi, Rapheal Abiodun; Oyeyipo, Opeyemi Olanrewaju; Afolabi, Adedeji (Penerbit Universiti Sains Malaysia, 2017)
Due to the alarming rate of building collapse, this study assesses building control practices in Lagos state. It examines the effectiveness of building control practices, and it also identifies the factors limiting the capacity of building control practices. To achieve these objectives, quantitative techniques were used in which 61 questionnaires were distributed to selected professionals from contracting firms within the built environment. The sample was selected using the purposive sampling technique. The data collected were processed using mean item score, percentage and ANOVA. The study revealed that not all building control measures were thoroughly observed. It was discovered from the findings that, aside from the measure of processing and scrutinising the building plans for approval, which was duly observed, no other measures were observed, and they are all equally significant. The study also identifies factors that impede adherence to building control practices, such as corruption and the bureaucratic process, which were ranked highest. Hypothesis testing revealed that there is no significant difference among the professionals in their perception of the effectiveness of building control practices. In conclusion, this study recommends regular auditing of the activities of building control agencies due to the prevalence of corruption cases among their members.